The identity politics of the local head election in Bolaang Mongondow, Indonesia - Kimbal, Alfons; Rompas, Jufri (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
Democracy in Indonesia should be a place to channel the aspirations of the people according to their preferences. The identity politics is a strategy carried out by interested groups in a contestation, the goal is to gain sympathy and votes in the election. However, the impact of the the identity politics tends to be negative where people tend to be selfish for one and group’s sake and this is contrary to Pancasila and the 1945 Constitution. Bolaang Mongondow Regency is the locus of this research, where this area is still thick with the phenomenon of identity politics. This research examines the phenomenon of the the identity politics for election participants and also its impact on society as well as data found in the field and also previous studies that have examined matters related to the title of this research and then conducted a focus of group discussions. From the results of the study, it was found that the Identity Political Behavior in the Bolaang Mongondow Regency, especially in the Election of The Regional Heads in 2017 is still within the level of reasonableness and is one of the political strategies of the candidate pairs but is still within reasonable limits and it can be seen that there is no longer a majority force that has a sectoral ego in the interests of power but also the community has matured in choosing their leaders in the elections.